Gender perceptions in political speech: women and political style - Rizqi Fitrianti; Luis Fiska Rahayu; Eli Apud Saepudin (The International Journal of Politics and Sociology Research, 2023)
The patriarchal culture in Indonesia has given women the image that they are only suitable for the domestic area, and men are the main actors in the household, as a head of household. This makes women less likely to have a career in life, especially in politics. So far, the affirmative policy on the 30% quota for women to participate in politics has brought women to continue to develop and move to play a role in the public space. The problem that will be discussed in this research is the stigma in society and the limitations of women's roles in the political arena that have been attached to patriarchy. In this research, it aims to bring women to a more open stigma, that women can have a role in the public space just like men. The method used in this research is the ethnomedia method with a descriptive qualitative approach. The ethnomedia method is used as a reference for researchers in collecting data in the mass media, which can provide references that can provide various long angles. From this research, it can be concluded that despite the inherent patriarchal culture in Indonesia, women today can have brilliant careers in the public sector. Some Indonesian women politicians have proven that women can also be role models, provide the right policies, have charisma in leading and be a good example for the society.